Self-Efficacy and Independent Learning in Students’ Learning Motivation: Efikasi Diri dan Pembelajaran Mandiri dalam Motivasi Belajar Siswa - Ramandha, Jesia; LAILI, NURFI (Indonesian Journal of Education Methods Development, 2025)
General background: Motivation is a crucial factor in students’ academic success, especially in the context of boarding schools where learning environments shape character and discipline. Specific background: However, many students still struggle with low motivation due to limited self-efficacy and inadequate independent learning skills, which hinder optimal academic achievement. Knowledge gap: While previous studies have examined self-efficacy or independent learning separately, few have analyzed their combined role in shaping students’ motivation at the junior secondary boarding school level. Aims: This study investigates how self-efficacy and independent learning contribute to students’ learning motivation at SMP Muhammadiyah 5 Tulangan. Results: Using a saturated sample of 75 students across grades 7 to 9 and analyzing data with multiple linear regression, the findings show that self-efficacy and independent learning significantly predict learning motivation (F=56.838; p<0.001), explaining 62.1% (R²=0.612) of its variance. Novelty: The study demonstrates that the synergy of self-efficacy and independent learning provides stronger explanatory power for student motivation compared to analyzing them in isolation. Implications: Strengthening these two factors may offer educators practical strategies to foster motivation and academic engagement in Islamic boarding school settings. Highlights: Self-efficacy and independent learning jointly shape students’ learning motivation. The model explains 62.1% of motivation variance among boarding school students. Offers insights for strategies to strengthen motivation in Islamic education contexts. Keywords: Self-Efficacy, Independent Learning, Motivation, Boarding School, Secondary Education